THE DEVELOPMENT OF INTEGRATED CURRICULUM TO FORM SPIRITUALITY AND INTELLECTUALITY STUDENTS - Abidin, Zainal; Salih, Badrus (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
Islamic boarding schools are a type of complementary religious education institution for formal educational institutions and a form of transforming Islamic values ​​to Islamic generations. The demands of the times and society require innovation. Educational innovation concerns hardware and software aspects of Islamic boarding schools so that students are not out of date. This research study uses a type of field research and uses a descriptive-qualitative paradigm. The data collection used is the method of observation, interviews, comments. The collected data is then analyzed using data collection methods, data presentation, data reduction, and data verification. The results of this study indicate that the Darul Ilmi Islamic Boarding School in shaping the spirituality and intellectuality of the students with integrated curriculum management requires planning, implementation and evaluation. Curriculum planning in shaping the spiritual and intellectual intelligence of students at Darul Ilmi Islamic Boarding School is based on the motto, vision, mission and, objectives of the pesantren. The implementation of an integrated curriculum at the Darul Ilmi Islamic Boarding School in shaping the spirituality and intellectuality of the students is carried out together with the Head of Dirosahan in making curriculum programs at the class level, Islamic boarding school curriculum and class level Permendiknas curriculum as well as activities outside the classroom, as well as conducting curriculum development to all asatidz through work meetings. While the curriculum evaluation carried out by Darul Ilmi Islamic Boarding School is based on several things, namely: based on needs and suitability, and based on proposals based on semester exam results and observations made by homeroom teachers and other assistants.